Efficiency wages and bargaining - Frank Walsh (University College Dublin, UCD School of Economics, 2005)
I argue that in contrast to the literature to date efficiency wage and bargaining solutions will typically be independent. If the bargained wage satisfies the efficiency wage constraint efficiency wages are irrelevant. If it does not, typically we have the efficiency wage solution and bargaining is irrelevant.
hdl:10197/192
Keywords: 330